1997
DOI: 10.1086/303654
|View full text |Cite
|
Sign up to set email alerts
|

Dense Gas and Star Formation: Characteristics of Cloud Cores Associated with Water Masers

Abstract: We have observed 150 regions of massive star formation, selected originally by the presence of an H 2 O maser, in the J = 5→4, 3→2, and 2→1 transitions of CS, and 49 regions in the same transitions of C 34 S. Over 90% of the 150 regions were detected in the J = 2→1 and 3→2 transitions of CS and 75% were detected in the J=5→4 transition. We have combined the data with the J = 7→6 data from our original survey (Plume et al. 1992) to determine the density by analyzing the excitation of the rotational levels. Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
330
5
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(376 citation statements)
references
References 58 publications
(68 reference statements)
39
330
5
2
Order By: Relevance
“…The presence of an envelope around the IRAS sources is confirmed by their association with high-density gas, and the existence of hot gas by the detection of a hot core and water or methanol masers (e.g. Bronfman et al 1996;Plume et al 1997). In this way, studies by e.g., Molinari et al (2000) and Sridharan et al (2002) have identified massive young stellar objects harboring highluminosity infrared protostars (see also Mueller et al 2002;Faúndez et al 2004).…”
mentioning
confidence: 84%
“…The presence of an envelope around the IRAS sources is confirmed by their association with high-density gas, and the existence of hot gas by the detection of a hot core and water or methanol masers (e.g. Bronfman et al 1996;Plume et al 1997). In this way, studies by e.g., Molinari et al (2000) and Sridharan et al (2002) have identified massive young stellar objects harboring highluminosity infrared protostars (see also Mueller et al 2002;Faúndez et al 2004).…”
mentioning
confidence: 84%
“…The objects in this study were selected from the sample of Plume, Jaffe, & Evans (1992) and Plume et al (1997) of massive star-forming cores associated with water masers. Table 1 lists the sources and their observed properties.…”
Section: The Samplementioning
confidence: 99%
“…This result does not apply to unbound clumps in GMCs, which can have lower column densities [5], nor to the OB star-forming clumps studied by Plume et al [87], which haveN H22 ∼ 60.…”
Section: Dynamical Propertiesmentioning
confidence: 68%
“…Thus, the dynamically regulated rate appears to be within the range observed in these clumps assuming that the star formation has been occurring for the past 1-3 Myr. The OB star-forming clumps observed by Plume et al [87] are an order of magnitude more massive than these, and it is not known if their properties are also consistent with dynamically regulated star formation.…”
Section: Dynamical Evolution Of Gmcsmentioning
confidence: 87%